Reformasi Administrasi di Korea Selatan: Sebuah Pembelajaran Kesuksesan - Seno, Ramadhani Haryo (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2020)
This research examined the strategy and process of administrative reform in South Korea. The method was using a descriptive qualitative approach with analysis of literature study from secondary data. The results showed that there were six strategies in South Korea administrative reform, i.e.: (1) downsizing; (2) deregulations; (3) reorganization; (4) administrative efficacy; (5) debureaucratization; and (6) decentralization. Downsizing was applied to shrink government institutions in every regime. Deregulations was applied through business privatization and economic liberalization to escape from economic crisis. Reorganization was applied by merging several government institutions to improve the communication process and public service. Administrative efficacy was applied through utilizing and improving e-government in public service. Debureaucratization was applied toward civil servants to promote professional and competent bureaucrats. Decentralization was applied to shorten the decision making process and create contextual local-government policy.